A RESULT OF THE APPROPRIATENESS OF SUPPLEMENTARY FOOD PROVISION (PMT) IN CASES OF STUNTING IN THE WORK AREA OF THE BATUDAA PANTAI PUBLIC HEALTH CENTER GORONTALO REGENCY - Cica N Akuba; Srikit S Nurkamiden; Deby Sinta Darise (Persatuan Dosen Kesehatan Masyarakat, 2026)
Stunting remains a serious health problem, including in the working area of the Batudaa Pantai Health Center. This condition arises from chronic malnutrition from the prenatal period through early life, which impacts linear growth, cognitive development, and the child's immune system. Based on the 2023 health center report, stunting cases remain, and interventions such as Supplementary Feeding (PMT) are not yet optimal. This situation highlights the need for a thorough evaluation of PMT implementation as part of efforts to improve the nutrition of young children. Stunting remains a serious health problem, including in the working area of the Batudaa Pantai Health Center. This condition arises from chronic malnutrition from the prenatal period through early life, which impacts linear growth, cognitive development, and the child's immune system. Based on the 2023 health center report, stunting cases remain, and interventions such as Supplementary Feeding (PMT) are not yet optimal. This situation highlights the need for a thorough evaluation of PMT implementation as part of efforts to improve the nutrition of young children. Based on the research findings, this study concludes that the implementation of the Supplementary Feeding Program (PMT) in the Batudaa Pantai Public Health Center's working area has been quite successful in terms of target accuracy, food type, and quantity. However, improvements are still needed in terms of timeliness, frequency of administration, and children's consumption levels of PMT. The research results show that target accuracy and PMT consumption levels are significantly related to children's nutritional status. Children who receive PMT accurately and consume it regularly show better nutritional status compared to children who do not receive it accurately or do not consume PMT regularly. Keywords: PMT Accuracy, Stuntin